The effect of combined supplementation of carbohydrates and creatine on anaerobic performance - Theodorou, AS; Paradisis, G; Smpokos, E; Chatzinikolaou, A; Fatouros, I; King, RFGJ; Cooke, CB (Biology of Sport, 2017)
The purpose of the study was to examine the effect of creatine (Cr) supplementation on anaerobic performance when ingesting creatine and carbohydrates (CHO) together. Twenty male physical education students comprised the two experimental (CR and CRCHO) and one control (CON) groups of the study. All groups performed three 30 s anaerobic Wingate tests (AWTs) interspersed with 6 minutes of recovery. The CR group (n = 7) ingested 5 g of Cr 5 times per day for 4 days. Subjects in the CRCHO group (n = 6) ingested the same quantity but additionally after each 5 g dose of Cr consumed 500 ml of a commercially available energy drink containing 100 g of simple sugars. Over all three AWTs average mean power improved significantly compared to baseline for the CR group (5.51%) but not for the CRCHO group (3.06%). Mean power for the second AWT was improved following the acute loading for the CR group only (4.54%) and for the third AWT for both CR (8.49%) and CRCHO (5.75%) groups. Over all three AWTs a significant change was recorded in average peak power following the acute loading for the CR group (8.26%) but not for the CRCHO group (4.11%). Peak power was significantly improved following the loading only for the CR group during the third AWT (19.79%). No changes in AWT performance were recorded for the CON group after intervention. The findings of the present study suggest that ingesting creatine together with carbohydrates will not further improve performance compared to the ingestion of creatine only.